High-tolerance crystalline hydrogels formed from self-assembling cyclic dipeptide - You, Yongcai; Xing, Ruirui; Zou, Qianli; Shi, Feng; Yan, Xuehai (Beilstein Journal of Nanotechnology, 2019)
Peptide-based supramolecular hydrogels, as a new type of biological nanoarchitectonic structure, hold great promise for a wide range of biomedical and nanotechnological applications, such as tissue engineering, drug delivery, and electronic and photonic energy storage. In this work, a cyclic dipeptide (CDP) cyclo-(Trp-Tyr) (C-WY), which has exceptional structural rigidity and high stability, is selected as a hydrogelator for the formation of supramolecular hydrogels. The unique hydrogen bonding in C-WY endows a high propensity for self-assembly and the resulting hydrogels are revealed to be crystalline. The crystalline hydrogels possess excellent mechanical capacity and superior tolerance to various harsh conditions, including in the presence of charged biopolymers, extreme acid/base environments, and changing thermal conditions. Such high tolerance enables the crystalline hydrogels to be applied in the complex and harsh environments of electrochemistry. In addition, this study demonstrates that the self-assembly of cyclic dipeptides results in highly robust hydrogels which can be applied for electrochemical applications such as electrochemical supercapacitors.
Keywords: crystalline hydrogel; cyclic dipeptide; electrochemical supercapacitors; nanoarchitectonics; self-assembly

(untitled) - Jackman, J. A.; Cho, N.-J.; Nishikawa, M.; Yoshikawa, G.; Mori, T.; Shrestha, L. K.; Ariga, K. (Chem. – Asian J., 2018)

(untitled) - Cringoli, M. C.; Kralj, S.; Kurbasic, M.; Urban, M.; Marchesan, S. (Beilstein J. Nanotechnol., 2017)

(untitled) - Billiet, T.; Vandenhaute, M.; Schelfhout, J.; Van Vlierberghe, S.; Dubruel, P. (Biomaterials, 2012)

(untitled) - Zhao, L.; Zou, Q.; Yan, X. (Bull. Chem. Soc. Jpn., 2019)

(untitled) - Hong, S.; Lee, H.; Lee, H. (Beilstein J. Nanotechnol., 2014)

(untitled) - Pan, L.; Yu, G.; Zhai, D.; Lee, H. R.; Zhao, W.; Liu, N.; Wang, H.; Tee, B. C.-K.; Shi, Y.; Cui, Y.; Bao, Z. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Komiyama, M.; Yoshimoto, K.; Sisido, M.; Ariga, K. (Bull. Chem. Soc. Jpn., 2017)

(untitled) - Ariga, K.; Watanabe, S.; Mori, T.; Takeya, J. (NPG Asia Mater., 2018)

(untitled) - Zhang, Y.; Zhang, H.; Zou, Q.; Xing, R.; Jiao, T.; Yan, X. (J. Mater. Chem. B, 2018)

(untitled) - Xing, R.; Liu, K.; Jiao, T.; Zhang, N.; Ma, K.; Zhang, R.; Zou, Q.; Ma, G.; Yan, X. (Adv. Mater. (Weinheim, Ger.), 2016)

(untitled) - Shen, G.; Xing, R.; Zhang, N.; Chen, C.; Ma, G.; Yan, X. (ACS Nano, 2016)

(untitled) - Xing, R.; Jiao, T.; Yan, L.; Ma, G.; Liu, L.; Dai, L.; Li, J.; Möhwald, H.; Yan, X. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Xing, R.; Li, S.; Zhang, N.; Shen, G.; Möhwald, H.; Yan, X. (Biomacromolecules, 2017)

(untitled) - Wang, J.; Liu, K.; Xing, R.; Yan, X. (Chem. Soc. Rev., 2016)

(untitled) - Reches, M.; Gazit, E. (Curr. Nanosci., 2006)

(untitled) - Zou, Q.; Abbas, M.; Zhao, L.; Li, S.; Shen, G.; Yan, X. (J. Am. Chem. Soc., 2017)

(untitled) - Hamley, I. W. (Soft Matter, 2011)

(untitled) - Hartgerink, J. D.; Beniash, E.; Stupp, S. I. (Science, 2001)

(untitled) - Salaam, A. D.; Hwang, P.; McIntosh, R.; Green, H. N.; Jun, H.-W.; Dean, D. (Beilstein J. Nanotechnol., 2014)

(untitled) - Liu, K.; Xing, R.; Zou, Q.; Ma, G.; Möhwald, H.; Yan, X. (Angew. Chem., Int. Ed., 2016)

(untitled) - Zhang, S.; Marini, D. M.; Hwang, W.; Santoso, S. (Curr. Opin. Chem. Biol., 2002)

(untitled) - Abbas, M.; Zou, Q.; Li, S.; Yan, X. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Xing, R.; Yuan, C.; Li, S.; Song, J.; Li, J.; Yan, X. (Angew. Chem., Int. Ed., 2018)

(untitled) - Li, G.; Li, S.; Sun, J.; Yuan, Z.; Song, A.; Hao, J. (Colloids Surf., A, 2018)

(untitled) - Cui, H.; Webber, M. J.; Stupp, S. I. (Biopolymers, 2010)

(untitled) - Ren, X.; Zou, Q.; Yuan, C.; Chang, R.; Xing, R.; Yan, X. (Angew. Chem., Int. Ed., 2019)

(untitled) - Yan, X.; Cui, Y.; Qi, W.; Su, Y.; Yang, Y.; He, Q.; Li, J. (Small, 2008)

(untitled) - Song, J.; Xing, R.; Jiao, T.; Peng, Q.; Yuan, C.; Möhwald, H.; Yan, X. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Ariga, K.; Li, J.; Fei, J.; Ji, Q.; Hill, J. P. (Adv. Mater. (Weinheim, Ger.), 2016)

(untitled) - Abbas, M.; Xing, R.; Zhang, N.; Zou, Q.; Yan, X. (ACS Biomater. Sci. Eng., 2018)

(untitled) - Jayawarna, V.; Ali, M.; Jowitt, T. A.; Miller, A. F.; Saiani, A.; Gough, J. E.; Ulijn, R. V. (Adv. Mater. (Weinheim, Ger.), 2006)

(untitled) - Chronopoulou, L.; Toumia, Y.; Cerroni, B.; Gentili, A.; Paradossi, G.; Palocci, C. (Colloids Surf., A, 2017)

(untitled) - Ma, D.; Zhou, N.; Zhang, T.; Hu, K.; Ma, X.; Gu, N. (Colloids Surf., A, 2017)

(untitled) - Mahler, A.; Reches, M.; Rechter, M.; Cohen, S.; Gazit, E. (Adv. Mater. (Weinheim, Ger.), 2006)

(untitled) - Yan, C.; Altunbas, A.; Yucel, T.; Nagarkar, R. P.; Schneider, J. P.; Pochan, D. J. (Soft Matter, 2010)

(untitled) - Yu, Z.; Xu, Q.; Dong, C.; Lee, S.; Gao, L.; Li, Y.; D'Ortenzio, M.; Wu, J. (Curr. Pharm. Des., 2015)

(untitled) - Adhikari, B.; Banerjee, A. (Soft Matter, 2011)

(untitled) - Manchineella, S.; Govindaraju, T. (ChemPlusChem, 2017)

(untitled) - Madhu, C.; Voshavar, C.; Rajasekhar, K.; Govindaraju, T. (Org. Biomol. Chem., 2017)

(untitled) - Jeziorna, A.; Stopczyk, K.; Skorupska, E.; Luberda-Durnas, K.; Oszajca, M.; Lasocha, W.; Górecki, M.; Frelek, J.; Potrzebowski, M. J. (Cryst. Growth Des., 2015)

(untitled) - Furukawa, T.; Akutagawa, T.; Funatani, H.; Uchida, T.; Hotta, Y.; Niwa, M.; Takaya, Y. (Bioorg. Med. Chem., 2012)

(untitled) - Bellezza, I.; Peirce, M. J.; Minelli, A. (Trends Mol. Med., 2014)

(untitled) - Hanabusa, K.; Matsumoto, Y.; Miki, T.; Koyama, T.; Shirai, H. (J. Chem. Soc., Chem. Commun., 1994)

(untitled) - Yan, X.; Su, Y.; Li, J.; Früh, J.; Möhwald, H. (Angew. Chem., Int. Ed., 2011)

(untitled) - Hanabusa, K.; Matsumoto, M.; Kimura, M.; Kakehi, A.; Shirai, H. (J. Colloid Interface Sci., 2000)

(untitled) - Hoshizawa, H.; Suzuki, M.; Hanabusa, K. (Chem. Lett., 2011)

(untitled) - Wang, P.; Zakeeruddin, S.; Exnar, I.; Gratzel, M. (Chem. Commun., 2002)

(untitled) - Yang, M.; Xing, R.; Shen, G.; Yuan, C.; Yan, X. (Colloids Surf., A, 2019)

(untitled) - Wang, J.; Yuan, C.; Han, Y.; Wang, Y.; Liu, X.; Zhang, S.; Yan, X. (Small, 2017)

(untitled) - Yan, C.; Pochan, D. J. (Chem. Soc. Rev., 2010)

(untitled) - Sun, J.; Guo, Y.; Xing, R.; Jiao, T.; Zou, Q.; Yan, X. (Colloids Surf., A, 2017)

(untitled) - Prasad, C. (Peptides, 1995)

(untitled) - Moreira, F. C.; Boaventura, R. A. R.; Brillas, E.; Vilar, V. J. P. (Appl. Catal., B, 2017)